Selective Estrogen Receptor Modulators: Cannabinoid Receptor Inverse Agonists with Differential CB1 and CB2 Selectivity - Franks, Lirit N.; Ford, Benjamin M.; Prather, Paul L. (Frontiers in Pharmacology, 2016)
Selective estrogen receptor modulators (SERMs) are used to treat estrogen receptor (ER)-positive breast cancer and osteoporosis. Interestingly, tamoxifen and newer classes of SERMs also exhibit cytotoxic effects in cancers devoid of ERs, indicating a non-estrogenic mechanism of action. Indicative of a potential ER-independent target, reports demonstrate that tamoxifen binds to cannabinoid receptors (CBRs) with affinity in the low μM range and acts as an inverse agonist. To identify cannabinoids with improved pharmacological properties relative to tamoxifen, and further investigate the use of different SERM scaffolds for future cannabinoid drug development, this study characterized the affinity and activity of SERMs in newer structural classes at CBRs. Fourteen SERMs from five structurally distinct classes were screened for binding to human CBRs. Compounds from four of five SERM classes examined bound to CBRs. Subsequent studies fully characterized CBR affinity and activity of one compound from each class. Ospemifine (a triphenylethylene) selectively bound to CB1Rs, while bazedoxifine (an indole) bound to CB2Rs with highest affinity. Nafoxidine (a tetrahydronaphthalene) and raloxifene (a benzothiaphene) bound to CB1 and CB2Rs non-selectively. All four compounds acted as inverse agonists at CB1 and CB2Rs, reducing basal G-protein activity with IC50 values in the nM to low μM range. Ospemifine, bazedoxifene and raloxifene also acted as inverse agonists to elevate basal intracellular cAMP levels in intact CHO-hCB2 cells. The four SERMs examined also acted as CB1 and CB2R antagonists in the cAMP assay, producing rightward shifts in the concentration-effect curve of the CBR agonist CP-55,940. In conclusion, newer classes of SERMs exhibit improved pharmacological characteristics (e.g., in CBR affinity and selectivity) relative to initial studies with tamoxifen, and thus suggest that different SERM scaffolds may be useful for development of safe and selective drugs acting via CBRs.